The Influence of IT Mastery, Networking and Business Capital on the Performance of MSMEs in the Jago Silo Blitar Community - Mukminiin, Ahmad Amiirul (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to analyze the influence of IT mastery, networking, and business capital on the performance of MSMEs in the Jago Silo community of Blitar City. With a population of 200 MSME members, a sample of 50 people was taken. Sampling follows the Arikunto (2012) method, where a sample is taken from 10-25% of the population if it amounts to more than 100 people. The results of the study show that IT mastery (X1), networking (X2), and business capital (X3) each have a significant influence on the performance of MSMEs. The IT mastery variable (X1) has a Sig value of 0.259 (> 0.05), networking (X2) 0.912 (> 0.05), and business capital (X3) 0.636 (> 0.05), so all hypotheses are accepted. Simultaneously, these three variables have a significant effect on the performance of MSMEs, shown by the values of Fcal = 6.257 and Sig = 0.001 (< 0.05). The determination coefficient of 97.4% showed that IT mastery, networking, and business capital contributed greatly to the performance of MSMEs, while 2.6% was influenced by other factors that were not studied. This research shows that these factors are very important in improving the performance of MSMEs in the Jago Silo Blitar community.